Urinary CXCL10 Chemokine Is Associated With Alloimmune and Virus Compartment-Specific Renal Allograft Inflammation. Issue 3 (March 2018) - Ho, Julie; Schaub, Stefan; Wiebe, Chris; Gao, Ang; Wehmeier, Caroline; Koller, Michael T.; Hirsch, Hans H.; Hopfer, Helmut; Nickerson, Peter; Hirt-Minkowski, Patricia
Abstract : Background: Urinary CXC chemokine ligand 10 (CXCL10) is a promising biomarker for subclinical tubulointerstitial inflammation, but limited data exist regarding its correlation with (micro)vascular inflammation. Furthermore, no study has evaluated whether concomitant serum CXCL10 improves the discrimination for (micro)vascular inflammation. Methods: We investigated whether serum/urinary CXCL10 reflect subclinical inflammation within different renal compartments. Patients (n = 107) with 107 surveillance biopsies were classified as: normal histology (n = 47), normal histology with polyomavirus BK (BKV) or cytomegalovirus (CMV) viremia (n = 17), moderate-severe tubulointerstitial inflammation (tubulitis ≥2, n = 18), pure microvascular inflammation (n = 15), and isolated v lesions (n = 10). Serum and urinary CXCL10 Enzyme-linked Immunosorbent Assay was performed. An independent validation set was evaluated for urine CXCL10: normal histology (n = 14), normal histology with BKV or CMV viremia (n = 19), tubulitis ≥2 (n = 15), pure microvascular inflammation (n = 41), and isolated v lesions (n = 14). Results: Elevated urinary CXCL10 reflected inflammation within the tubulointerstitial (urinary CXCL10/creatinine, 1.23 ng/mmol vs 0.46 ng/mmol; P = 0.02; area under the curve, 0.69; P = 0.001) and microvascular compartments (urinary CXCL10/creatinine, 1.72 ng/mmol vs 0.46 ng/mmol; P = 0.03; area under the curve, 0.69; P = 0.02) compared to normal histology. Intriguingly, urinary CXCL10 was predominantly elevated with peritubular capillaritis, but not glomerulitis ( P = 0.04). Furthermore, urinary CXCL10 corresponded with BKV, but not CMV viremia ( P = 0.02). These urine CXCL10 findings were confirmed in the independent validation set. Finally, serum CXCL10 was elevated with BKV and CMV viremia but was not associated with microvascular or vascular inflammation ( P ≥ 0.19). Conclusions: Urinary CXCL10 reflects subclinical inflammation within the tubulointerstitial and peritubular capillary spaces, but not the vascular/systemic compartments; this was consistent with BKV (tubulointerstitial) and CMV viremia (systemic). Serum CXCL10 was not a useful marker for (micro)vascular inflammation. Abstract : The authors dissect further the role of urinary CXCL10 as a biomarker of microinflammation due to rejection, BK and CMV viral infections but do not find any association with vascular/systemic compartments. Supplemental digital content is available in the text.